UJIAN ON LINE DALAM E-LEARNING: PERBANDINGAN UJIANONLINE (COMPUTER BASED) TERHADAP UJIAN TRADISIONAL (PAPER BASED) - Yuliyanto, Heri; Wahyuni, Titis; Seputra, Yulius Eka Agung (UI Scholars Hub, 2016)
Spreading the uneven quality education in Indonesia is a national educational problems to be solved. Implementation of quality education largely implemented in Java, in the case of Indonesian citizens spread all over Indonesia, from Sabang to Merauke. All citizens of the Indondesia want to receive a quality education that is easily accessible at reasonable costs. One solution that can be used to solve the problem is e-learning. However, many factors must be considered in the process of long-distance pembejaran known as elearning, one of which is the process of evaluating learning outcomes. This article discusses the process of evaluation of learning outcomes by studying literature several articles published between the years 2007 - 2015 with a focus on expert opinion to the statement